Research on influence of ICT application for teaching and learning mathematics in 4th form on School learners’ achievements - Gesevičienė, Vilma; Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2012)
Striving for identification of links between application of information communication technologies (ICT) in educational and learning environments and achievements in mathematics, a research on influence of application of these technologies for teaching and learning mathematics in 4th form on school students’ achievements was conducted. The article presents the main results of this research.